Pelatihan Pembuatan Eco-Enzyme dan Sabun Eco-Enzyme Daun Bidara Pada Santri Ponpes Bahrul Ulum Al-Fattah Gondang Legi - Mulyono, Agus; Wafiroh, Novi Lailiyul; Muthmainnah, Muthmainnah (JRCE (Journal of Research on Community Engagement), 2022)
Students who study at the Bahrul Ulum Gondanglegi Islamic boarding school do not have the skills to make their own herbal beauty products, especially soap, so there is a lot of waste just to buy beauty products that are getting more expensive. This underlies the need for introduction and training in making bidara leaf eco-enzyme and bidara leaf eco-enzyme herbal soap which has many benefits, especially for health and beauty. The methods carried out in this community service activity include socialization of the use and utilization of bidara leaves as efficacious plants and sunnahs, training on making bidara leaf eco-enzymes, and training on making herbal soap made from bidara leaf eco-enzymes. The training that has been given, was enthusiastically welcomed by all participants and caregivers of islamic boarding schools. Participants can follow the process of making bidara leaf eco-enzymes and the process of making herbal soaps made from bidara leaf eco-enzymes well, this is evidenced by the final product results that are well completed. In addition, the discussion containing questions and answers about the benefits of the products made is also very interesting. Participants asked a variety of good questions related to the eco-enzyme benefits of bidara leaves. In addition to personal use, it is hoped that mass production of herbal soap made from bidara leaf eco-enzyme can be carried out to be then marketed to the surrounding environment and be able to become one of the innovative products of pesantren that provides economic benefits.